2014
DOI: 10.5194/hess-18-2803-2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface wind speed decline on modeled hydrological conditions in China

Abstract: Abstract. Surface wind speed decline in China has been widely reported, but its effects on hydrology have not been fully evaluated to date. In this study, the effects of wind speed change on modeled hydrological conditions are investigated using the Variable Infiltration Capacity (VIC) hydrological model for China during the 1966-2011 period. Two model experiments, i.e., VIC simulations with the observed (EXP1) and detrended wind speed (EXP2), are performed over the major river basins in China. The differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 53 publications
4
30
0
Order By: Relevance
“…5). Liu et al (2014a) noted that the annual mean SWS decreased by more than 20% in most areas of China during the period 1966-2011. Guo et al (2011) found that the decreasing trend in the annual mean SWS in China reached − 0.18 m s −1 decade −1 and that the main contribution to this decrease in SWS came from the reduction of strong wind events.…”
Section: Asiamentioning
confidence: 99%
See 2 more Smart Citations
“…5). Liu et al (2014a) noted that the annual mean SWS decreased by more than 20% in most areas of China during the period 1966-2011. Guo et al (2011) found that the decreasing trend in the annual mean SWS in China reached − 0.18 m s −1 decade −1 and that the main contribution to this decrease in SWS came from the reduction of strong wind events.…”
Section: Asiamentioning
confidence: 99%
“…Studies have found that decreasing SWSs have significantly affected surface pan-evaporation over the Tibetan Plateau (TP), the Yellow River of China, and central and northern China over the last 30 years (Chen et al 2006;Zhang et al 2007;Liu and McVicar 2012). Furthermore, Liu et al (2011aLiu et al ( , 2014a concluded that the 29% decrease in SWS that has occurred in China in recent years has led to a 1-3% decrease in annual pan-evaporation and a 1-6% increase in runoff. Furthermore, this decrease in SWS accounted for 65% of the observed decrease in pan-evaporation during the period 1960-1991.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper on the situation in China showed that wind speed has declined by 25-30 % since the nineties (Liu et al, 2014) and a decrease of similar magnitude has been observed for the Cape region in South Africa (Hoffmann et al, 2011) and are implicated in the worldwide decrease in evaporative demand (McVicar et al, 2012). Data on wind speed are not easily available, but over the same time period, wind speed has not changed in several German regions (data not shown) and in some even an increase has been observed (Bormann, 2011), which could be part of the explanation of different trends for different areas.…”
Section: Observed Trends For Australian and California Regions (Summementioning
confidence: 99%
“…The VIC model used in this study was effectively calibrated and validated against observations in China at a spatial resolution of 0.25° [38], which has been well used in hydroclimatological studies [39][40][41] and climate impact assessments over China [42,43]. Specifically, we firstly derived a set of 61-year (1952-2012) daily gridded (0.25° × 0.25°) meteorological data by interpolating ground station observations from the China Meteorological Administration (CMA) [hereafter referred to as the Institute of Geographic Science and Natural Resources Research (IGSNRR) data].…”
Section: Model Descriptionmentioning
confidence: 99%